2007
DOI: 10.1371/journal.ppat.0030124
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dendritic Cells in Differential Susceptibility to Viral Demyelinating Disease

Abstract: Although persistent viral diseases are a global health concern, the mechanisms of differential susceptibility to such infections among individuals are unknown. Here, we report that differential interactions between dendritic cells (DCs) and virus are critical in determining resistance versus susceptibility in the Theiler murine encephalomyelitis virus–induced demyelinating disease model of multiple sclerosis. This virus induces a chronic demyelinating disease in susceptible mice, whereas the virus is completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
89
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(95 citation statements)
references
References 48 publications
6
89
0
Order By: Relevance
“…However, the levels of IFN-␥ production were similar in the presence or absence of added DCs across different concentrations of the cognate peptide (data not shown). The lack of significant deficiencies in the CNS APCs from virus-infected resistant B6 mice is consistent with our previous observation (20). Therefore, it is very unlikely that the differences in functional avidity presented in Fig.…”
Section: Vol 84 2010 Antiviral T-cell Repertoire In the Cns 2781supporting
confidence: 92%
“…However, the levels of IFN-␥ production were similar in the presence or absence of added DCs across different concentrations of the cognate peptide (data not shown). The lack of significant deficiencies in the CNS APCs from virus-infected resistant B6 mice is consistent with our previous observation (20). Therefore, it is very unlikely that the differences in functional avidity presented in Fig.…”
Section: Vol 84 2010 Antiviral T-cell Repertoire In the Cns 2781supporting
confidence: 92%
“…In addition, we have previously demonstrated that antigen-presenting cells (macrophages and dendritic cells) as well as microglia from susceptible SJL mice produce higher levels of type I IFNs, yet the viral replication levels are severalfold higher than those from resistant B6 mice (17,18). These results indicate that TMEV BeAn infection strongly induces type I IFNs in the presence of L protein and that viral replication is not interrupted in cells producing type I IFNs.…”
mentioning
confidence: 85%
“…In general, highaffinity CD8 ϩ T cells are preferentially tolerized by deletion or anergy in vivo. In fact, the relative levels of IFN-␥-producing cells upon stimulation with serial 10-fold-decreased epitope peptide concentrations indicated that functional avidity to the dominant epitope (VP3 159-166 ) is 50-and 100-fold higher than those to the subdominant epitopes (VP3 173-181 and VP1 [11][12][13][14][15][16][17][18][19][20] , respectively) (data not shown). These results are consistent with the preferential reduction of high-affinity VP3 159-166 -specific CD8 ϩ T cells over low-affinity subdominant epitope-reactive CD8 ϩ T cells.…”
Section: Sjl P1-tg Mice Immunized With Uv-tmev Exhibit Lower Levels Omentioning
confidence: 99%
See 1 more Smart Citation
“…TMEV infects a variety of cells both in the CNS and in the periphery, including macrophages, dendritic cells, microglia, and astrocytes (9)(10)(11)(12). Infection of cells with TMEV triggers a proinflammatory response consisting of type I interferons, tumor necrosis factor alpha (TNF-␣), interleukin-6 (IL)-6, and various chemokines (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%